Food on the Move - Murrell, Di (Petits Propos Culinaires, 2012)
This memoir recounts the way of life of the canal-boat families who used to carry freight on the inland waterways of Britain. A way of life which had, by the mid-twentieth century, become something of an anachronism, existing as it did in a world of fast new motorways and increasing consumerism. Its heyday, when the only competition was horse-drawn wagons and later the developing railway system, was fairly short – probably no more than 70 years. Nevertheless the nomadic existence of the canal families whose destinations were determined by the cargoes they loaded into the holds of their boats continued until the end of the 1960s when it was finished off by the big winter freeze of 1968/69.